PARTISIPASI ANGGOTA MENUJU KEMANDIRIAN USAHA KOPERASI - Endah SM (Jurnal Ilmiah Econosains, 2017)
ABSTRACTQuality of participation hardly determines in the effort reaching independence a co-operation; divided to become three participation variables that is member, management and program which can depict participation of member in cooperation service. Attainment of independence in co-operation requires time sufficiently long, because requires of legalistic process of growth; there are four phases which must be passed by in process of growth is started by attempt phase, fast development, level of growth downdraft and ends in the happening of stability or slump. To the four phases must can be passed by carefully so that will be able to yield independence in co-operation if condition of organization had stable.Keywords: Participation, Busines Independence.